Diagnosis of sensory and sensorimotor alalia: An integrated interdisciplinary approach - Denis Martyanov, Elena Gorobets, Tatyana Bolshakova, Faniya Zaykova,; Tsygankova, Anna (Opción, 2019)
The article describes the new interdisciplinary research launched at Kazan Federal University by the laboratory of clinical linguistics via interdisciplinary methodological basis. As a result, in Russian clinical practice there are no batteries of tests for speech evaluation containing linguistically validated materials, which will make it possible to objectify the results qualitatively and quantitatively. In conclusion, it is necessary to develop a consistent system of diagnosis and differential diagnosis, new Russian-language diagnostic psychometric instruments for children and questionnaires for their parents in order to identify specific markers of sensory alalia.